Benjamin Silliman correspondence - Silliman, Benjamin, 1779-1864.
ALS from Silliman to Campbell Morfit relating to Silliman's retirement from Yale.
Professor of chemistry at Yale University.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Morfit, Campbell, -- 1820-1897 -- Correspondence; Yale University -- Faculty; Chemists; Educators